Hemodynamic and Metabolic Responses to Ketamine and Etomidate Sedations During Endotracheal Intubation in Criticallyill Patients - Özlem Çınar; Arash Pirat; Pınar Zeyneloğlu; Aynur Camkıran; Nilüfer Bayraktar; Coşkun Araz; Gülnaz Arslan (Galenos Yayinevi, 2011)
Objective: The aim of this study was to compare the effects of etomidate and ketamine on hemodynamic and metabolic responses to intubation in ICU patients. Material and Method: After Clinical Research and Ethics Committee approval, 22 ICU patients who required intubation during their ICU stay were enrolled in this prospective, randomized, double-blinded study. Patients in group E (n=12) received etomidate 0.3 mg/kg IV and those randomized to group K (n=10) received ketamine 2 mg/kg IV for sedation during endotracheal intubation. Results: The demographic features, reasons for intubation and causes of ICU admission were similar between the groups (p>0.05). Mean heart rate and arterial blood pressure values were not significantly different between the two groups at the baseline and after intubation (p>0.05). Groups' mean serum cortisol and 11β-deoxycortisol concentrations were similar before and 5 minutes after intubation (p>0.05). The groups were not significantly different with regards to intubation conditions, mortality, length of ICU stay, and duration of mechanical ventilation (p>0.05). Mean sequential organ failure assesment (SOFA) scores during the first 9 days after intubation were also similar in both groups (p>0.05). Conclusion: Our results demonstrated that when used for endotracheal intubation of ICU patients, ketamine and etomidate are comparable in terms of hemodynamic and metabolic responses, intubation condition, and mean SOFA scores. (Journal of the Turkish Society Intensive Care 2011; 9: 77-84)